Level reading comprehension in English as a second language in university students - Flores, Salvador (2019)
The objective was to determine the level of reading comprehension in the area of English as a second language in the students of the third semester of Civil Engineering of the Universidad Andina "Néstor Cáceres Velásquez" of the city of Juliaca, 2018. We worked with a sample of 137 Students, to reach the objectives, the statistical table of frequencies has been used, within the framework of the Descriptive Statistics. It is concluded that more than half of the students understand the texts in English acceptably, since their grades range between 14 and 17 points (Expected Achievement). 5% of the students have difficulties to understand, they have notes of disapproval between 0 and 10 points. With respect to the literal level, almost half of the students have high levels of reading comprehension (solvent achievement), their grades oscillate between 18 and 20 points. With respect to the inferential level, almost half of the students are at the expected level of performance. His notes range between 14 and 17 points. In relation to the critical level, 44.5% of the students are located in the In process level, their grades vary between 11 and 13 points.